Optimization of pretreatment in delignification of hyacinth biomass for ethanol production - Effendi Nawawi; Zainal Fanani; Fakhili Gulo (Pascasarjana Universitas Negeri Medan, 2023)
Water hyacinth (Eichhornia crassipes) is one of the potential feedstocks for bioethanol production due to their higher cellulose content. It needs the optimization of pretreatment to remove lignin and release cellulose and hemicellulose from lignocellulosic complex. Pretreatment was done using sulfuric acid, sodium hydroxide, and calcium hypochlorite as soaking agents. Experiment was carried out at 121 °C for 15 minutes. Pretreatment with 1% sulfuric acid decreased lignin by 6.74%, 4.0% sodium hydroxide reduced lignin content by 11.23%, whereas pretreatment with 0.3% calcium hypochlorite removed lignin by 8.30% from original lignin content lignocellulosic substrate. Therefore, sodium hydroxide pretreatment showed highest efficacy in delignification processes, followed by calcium hypochlorite, and sulfuric acid pretreatments.Keywords: Lignin reduction; Lignocellulose; Pretreatment; Water hyacinth